The Influence of Relationship Marketing and Service Delivery on Customer Satisfaction and Customer Loyalty with Customer Engagement Behaviour as a Moderating Effect in Indonesia’s Internet Service Providers Industry - Bernardo Theonaldi; Fernando Theonaldi; Leonardo Theonaldi; Ario S Setiadi (Riviera Publishing, 2025)
This study investigates the influence of relationship marketing and service delivery on customer satisfaction and loyalty within Indonesia’s internet service provider industry, with customer engagement behaviour examined as a moderating variable. Given the growing competition in the internet service provider market, especially following the entry of satellite-based providers like Starlink, understanding factors that drive customer retention has become increasingly critical. Data were collected through a structured survey targeting students with extensive internet use, and analysis was conducted using Partial Least Squares Structural Equation Modelling. The findings reveal that both relationship marketing and service delivery significantly contribute to customer satisfaction and customer loyalty. Notably, customer engagement behaviour was found to moderate these relationships variably, enhancing the positive impact of service delivery on satisfaction but, in some cases, diminishing the effect of relationship marketing on loyalty. These results underscore the need for internet service providers to balance engagement strategies carefully and prioritize reliable, high quality service delivery to foster customer satisfaction and long-term loyalty. The study’s theoretical contributions extend the understanding of relationship marketing and customer engagement, while practical implications highlight strategies for internet service providers to remain competitive in Indonesia’s dynamic market.